Overcoming the Challenges of Logistics Outsourcing in Selected Oil and Gas Companies in Rivers State - Esima, Onyebueke Victoria; M. I, Ifeanacho; Wordu, Steve (International Journal of Scientific Research and Management (IJSRM), 2019)
Logistics outsourcing as a conscious business decision to move internal work or activities to an external supplier has become a means of minimizing cost, reducing internal workload and gaining core competency for organizations as well as Oil and Gas companies in recent times. In spite of the enormous advantages of logistics outsourcing as reported by previous studies such as cost reduction, effective base and warehouse management, improved safety, risk sharing, Knowledge transfer, training and development. However, research has shown that logistics outsourcing have, other times turned into a wellspring of corporate disappointment and dissatisfactions. In this work, the challenges that could lead to an unsuccessful logistics outsourcing were investigated to uncover the inherent challenges and recommend possible solutions to overcoming them. The sample size was focused on the managers and assistant managers in the selected oil and gas companies and their logistics providers. A total of 350 copies of questionnaire titled Logistics outsourcing and organizational performance questionnaire (LOOPQ) was designed and administered to elicit primary information and data from respondents who were chosen from the oil and gas companies and service providers with a 90% respondent rate. Secondary data was obtained from company records. The data for this study were analyzed using the Statistical Package for Social Sciences (SPSS) for both descriptive and inferential statistics.  The present study found that the failure of logistics outsourcing in the oil and gas companies can be connected to any of these challenges. The study have exposed the major challenges of logistics outsourcing in the oil and gas companies and recommended that a strategic management of logistics outsourcing which can overcome the challenges inherent in logistics outsourcing and improve organizational performance in the oil and gas industry should  include: Provision of New/Standard equipment and regular maintenance by logistics providers, Effective communication network between logistics providers and the selected oil and gas companies under study, provide motivation for members of staff, Advanced Customer/Client Relation Management, ensure good Quality Assurance and Control and effective monitoring of projects.